SOCIOECONOMIC STATUS IS GLOBALLY A PROGNOSTIC FACTOR FOR OVERALL SURVIVAL OF MULTIPLE MYELOMA PATIENTS; SYNTHESIS OF STUDIES AND REVIEW OF THE LITERATURE - Stergios Intzes; Marianthi Symeonidou; Konstantinos Zagoridis; Aikaterini Pentidou; Spanoudakis Emmanouil (Mediterranean Journal of Hematology and Infectious Diseases)
Socioeconomic status (SES) is reflecting differences in sociodemographic factors affecting cancer survivorship. Deprived, low SES populations has a higher prevalence of multiple myeloma and worst survival, a gap that widens over time.